PETROGENESIS OF PASIR CUPU DIORITE, PLERED DISTRICT, PURWAKARTA, WEST JAVA - Fachrudin, Kurnia Arfiansyah; Aini, Hana Nur; Syafri, Ildrem; Luthfi, Ahmad; Amitama, Emilia Bunga (Faculty of Geological Engineering, Universitas Padjadjaran, 2018)
Pasir Cupu located in the area of Plered and Sukatani, Purwakarta, West Java. It is geographically on 107o 26 '25.2' - 107o 27 '16.8' Easternmost and 6o 37 '22.8' - 6o 37 '03